PERSPECTIVES ON DEVELOPING THE BIOECONOMY SECOTOR IN ROMANIA - Pașculea, Marius (Annales Universitatis Apulensis Series Oeconomica, 2015)
In the context of the new aim of the European Bioeconomy Strategy and Action Plan the  development of the bioeconomy sector is a necessity for  Romania in order to pave the way to a more innovative, resource efficient and competitive society, that reconciles food security with the sustainable use o renewable resources for industrial purposes. Romania has good  perspectives in this field  due to a great potential of the agriculture, increasingly growing standards of food industry, applied research in the pharmaceutical industry,  safety and optimization of food products, the value of the biomass produced by the horticultural, forestry, livestock, fishery sectors and biofuels. On the premise that Romania hasn’t yet a bioeconomy strategy and/or policies in this field, the objective of this study is to identify the fundamental elements that could help Romanian Government build a customized bioeconomy strategy and/or plan of action.  The method used is based on analyzing the best practices used by countries that already trigged the development of their bioeconomy sectors. The result of this study is to offer a scientific base for theory and practice in the bioeconomy field.